Intra-testicular injection of adenoviral constructs results in Sertoli cell-specific gene expression and disruption of the seminiferous epithelium - Hooley, R P (2008)
Spermatogenesis is a complex process that cannot be modelled in vitro. The somatic Sertoli cells (SCs) within the seminiferous tubules perform a key role in supporting maturation of germ cells (GCs). Progress has been made in determining what aspects of SC function are critical to maintenance of fertility by developing rodent models based on the Cre/LoxP system; however, this is time-consuming and is only applicable to mice. The aim of the present study was to establish methods for direct injection of adenoviral vectors containing shRNA constructs into the testis as a way of inducing target-selective knock-down in vivo. This paper describes a series of experiments using adenovirus expressing a green fluorescent protein (GFP) transgene. Injection via the efferent ductules resulted in SC-specific expression of GFP; expression levels paralleled the amount of infective viral particles injected. At the highest doses of virus seminiferous tubule architecture were grossly disturbed and immune cell invasion noted. At lower concentrations, the expression of GFP was variable/negligible, the seminiferous tubule lumen was maintained but stage-dependent GC loss and development of numerous basal vacuoles was observed. These resembled intercellular dilations of SC junctional complexes previously described in rats and may be a consequence of disturbances in SC function due to interaction of the viral particles with the coxsackie/adenovirus receptor that is a component of the junctional complexes within the blood testis barrier. In conclusion, intra-testicular injection of adenoviral vectors disturbs SC function in vivo and future work will therefore focus on the use of lentiviral delivery systems.